Transforming Elementary School Children's Interest in Reading in Jompie Village Through the LINE (Infinite Literacy) Program: Transformasi Minat Baca Anak-anak Sekolah Dasar di Desa Jompie Melalui Program LINE (Literasi Infinite) - Ja’faruddin, Ja’faruddin; Irwan, Irwan; Hamzi, Zaidulkhair; Sukmawati, Sukmawati; Yusri, Muhammad (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Reading is an act that opens the door to knowledge and new information for individuals. However, the interest in reading in Indonesia has a concerning record. Indonesia ranks 60th out of 61 countries in the reading interest index. UNESCO data shows that only 0.001% of Indonesia's population actively reads. Factors such as the lack of school libraries, limited budgets, and the impact of technology have contributed to the low reading interest, especially among students. The LINE Program is an initiative by the UNM 2023 KKNT team aimed at increasing the reading interest of elementary school children in Jompie Village. This program uses participatory observation methods to understand children's interaction with books and literacy. The LINE program has successfully achieved positive results. Children's reading interest has increased, they have developed reading skills, taken the initiative to read independently, expanded their vocabulary, and gained a deeper understanding. This program also promotes lifelong learning. The LINE program has transformed children into diligent and initiative readers, providing long-term benefits in their literacy and education development. In efforts to increase reading interest in Indonesia, initiatives like this are crucial to be implemented nationwide. Abstrak Membaca merupakan tindakan yang membuka pintu pengetahuan dan informasi baru bagi individu. Namun, minat membaca di Indonesia memiliki catatan yang mengkhawatirkan. Indonesia menduduki peringkat ke-60 dari 61 negara dalam indeks minat membaca. Data UNESCO menunjukkan bahwa hanya 0,001% dari penduduk Indonesia yang aktif membaca. Faktor-faktor seperti kurangnya perpustakaan sekolah, anggaran terbatas, dan dampak teknologi telah berkontribusi pada rendahnya minat baca, terutama di kalangan siswa. Program LINE adalah inisiatif tim KKNT UNM 2023 yang bertujuan untuk meningkatkan minat baca anak-anak sekolah dasar di Desa Jompie. Program ini menggunakan metode observasi partisipatif untuk memahami interaksi anak-anak dengan buku dan literasi. Program LINE telah berhasil mencapai hasil positif. Minat baca anak-anak telah meningkat, mereka telah mengembangkan keterampilan membaca, mengambil inisiatif membaca mandiri, meningkatkan kosakata, dan mendapatkan pemahaman yang lebih mendalam. Program ini juga mendorong pembelajaran seumur hidup. Program LINE telah mengubah anak-anak menjadi pembaca rajin dan inisiatif, memberikan manfaat jangka panjang dalam perkembangan literasi dan pendidikan mereka. Dalam upaya meningkatkan minat baca di Indonesia, inisiatif seperti ini sangat penting untuk diterapkan di seluruh negeri.